Urgency of Contract Model Settings in the Global Digital Market Related To Tourism Business: A Study on Consumer Protection and Electronic Information and Transactions - Deli Bunga Saravistha; I Ketut Sukadana; Kadek Dedy Suryana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Globalization has now penetrated various sectors, including the Tourism Business Sector. One of the characteristics is the process of digitization in all fields, which in turn brings about changes in the implementation of the law. This paper will discuss the issue of optimizing consumer protection in the context of the emergence of new contract forms, namely standard digital contracts in the business world and the presence of a new cross-borderless market mechanism, known as the Digital Global Market or Marketplace. This research will formulate two issues related to how to regulate consumer protection policies for users of the global digital market platform services about dispute resolution? Then about how to model digital contract arrangements as an effort to optimize consumer protection? Where the writing uses a normative research method, either through the approach of legislation, cases, comparisons, and comparisons, which are presented descriptively, evaluatively, and presenting arguments that are expected to be able to contribute ideas for legal development in the world of tourism business.